2018
DOI: 10.3897/mycokeys.38.27014
|View full text |Cite
|
Sign up to set email alerts
|

Ophiostomatoid fungi associated with pines infected by Bursaphelenchus xylophilus and Monochamus alternatus in China, including three new species

Abstract: The activity of the pine wood nematode Bursaphelenchusxylophilus leads to extremely serious economic, ecological and social losses in East Asia. The nematode causes pine wilt disease, which is currently regarded as the most important forest disease in China. The pathogenic nematode feeds on dendrocola fungi to complete its cycle of infection. As the vector of the nematode, the Japanese pine sawyer (Monochamusalternatus) also carries dendrocola fungi. Pine woods, infected by B.xylophilus and tunnelled by M.alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…This suggested that A. saccharicola has low host specificity. Additionally, A. arundinis , A. marii , and A. sacchari have been isolated from more than one substrate in another study [7]. A. arundinis has been isolated from the leaf of Hordeum vulgare and living leaves of Fagus sylvatica in Iran and Switzerland [4].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggested that A. saccharicola has low host specificity. Additionally, A. arundinis , A. marii , and A. sacchari have been isolated from more than one substrate in another study [7]. A. arundinis has been isolated from the leaf of Hordeum vulgare and living leaves of Fagus sylvatica in Iran and Switzerland [4].…”
Section: Resultsmentioning
confidence: 99%
“…A. arundinis has been isolated from the leaf of Hordeum vulgare and living leaves of Fagus sylvatica in Iran and Switzerland [4]. Additionally, in a recent study, 19 strains of A. arundinis were isolated from nine different hosts in China [7]. Taxonomical work on Arthrinium species isolated from marine ecosystems has been relatively lacking compared to work on those isolated from terrestrial ecosystems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, 98 ophiostomatoid species, including 49 new species, have been reported in association with bark beetles from China (Table S1) (Lu et al 2009a(Lu et al , 2009bPaciura et al 2010aPaciura et al , 2010bZhou et al 2011Zhou et al , 2013Taerum et al 2013;Yin et al 2015Yin et al , 2016Yin et al , 2019Yin et al , 2020Wang et al 2016Wang et al , 2018Wang et al , 2019Wang et al , 2020Chang et al 2017Chang et al , 2019Liu et al 2017). The study by Chang et al (2017) was the first to report ophiostomatoid fungi associated with phoretic mites.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, in terms of diseases and insect pests, among the four main tree species, pine was most seriously affected by insect pests. Pine caterpillars, bumblebees, Alternaria alternata and other pests basically take pines as the invasion object, which makes the growth of pines weak [23].…”
Section: Discussionmentioning
confidence: 99%